PERAN PEMERINTAH DAERAH DALAM PENGELOLAAN SEKTOR PERTANIAN MELALUI BALAI PENYULUHAN PERTANIAN DI KECAMATAN WONOMULYO KABUPATEN POLEWALI MANDAR - Nur Fachri Kurniawan; Rustan IR (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
The purpose of this study was to find out how the role of the Regional Government in managing the agricultural sector through the Agricultural Counseling Center in Wonomulyo Subdistrict, Polewali Mandar Regency. The type of research used is qualitative, namely the author describes and analyzes the data studied or obtained in the field, both primary data obtained from the results of observations or interviews, as well as from secondary data. The results of this study indicate that the role of the Agricultural Extension Center in improving the welfare of farmers in Wonomulyo Subdistrict has been quite good. The Agricultural Counseling Center acts as a Motivator, Educator, Facilitator, and Change Agent. This is supported by supporting factors and inhibiting factors.